Leksyka Nowego Testamentu Biblii brzeskiej (1563) oraz Biblii Jakuba Wujka (1599) wobec zasobu leksykalnego Słownika polszczyzny XVI wieku - Lisowski, Tomasz (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2010)
The analysis presented in the paper consists in juxtaposition of the listing of the entries from the New Testament of Brześć Bible (1563) and the New Testament of the Bible of Jakub Wujek (1599), two sixteen-century translations of the Bible, distinguished by their great social influence, with the index of the entries of hitherto published volumes of the Dictionary of the Polish Language of the 16th Century, the wordbook which presents the condition of the vocabulary of the sixteen-century Polish. The two biblical translations provided 14 lexemes unrecorded as entries in the Dictionary. Firstly, there are morphological variants among them of the entries of the Dictionary – 4 lexemes, (e.g., huf); secondly, derivatives from the entries of the Dictionary – 3 lexemes (e.g., potaić się); thirdly, the lexemes being grammatical forms stemming from the entries in the Dictionary – 5 lexemes (e.g., gardzony), the meaning of some of them departs from the meaning of their basic grammatical form; fourthly, the lexemes which are not morphological variants of the entries of the Dictionary – 2 lexemes of foreign origin (e.g., afryk). All of the mentioned lexemes are marginal with respect to typical lexical resources of the sixteenth-century Polish. Some of them, however, (e.g., pomorze), became popular in the seventeenth-century Polish, which attests to the transformations of the Polish lexis in that century.